PERTUMBUHAN LANJUT AKSESI DOYO (Curculigo latifolia) HASIL DOMESTIKASI - Candra Catur Nugroho; Erwin Arief Rochyat (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2019)
Doyo plants are expected to produce offspring or generations that are able to adapt well in a new growing environment. The generation of doyo accessions that managed to grow well in the new environment was then passed on as propagation material to produce the next generation so that a large number of plant propagation materials were obtained for large-scale cultivation. This study aims to observe the continued growth of doyo accessions as a result of domestication. This research consisted of two experiments. The first experiment was to see the growth of tillers from 6 doyo accessions (Tenggarong, Kota Bangun, Muara Wis, Jempang, Bongan, Anggana). The second experiment was to see the growth of the first generation of doyo accessions from domestication. The planting material used was tillers of doyo accession originating from the first experiment grouped into 3 groups based on the age of the tillers: group 1 (0 - <3 months), group 2 (3 - <5 months), group 3 (5 - <7 months). Data in the first and second experiments were analyzed by the F-test (α=95%) and then tested further using the DMRT (Duncan Multiple Range Test) test using SAS v. 11.6 software. In the first experiment, the analysis showed that the treatment of accession had no significant effect on the number of tillers at 3 to 6 months after planting (MAP), but had a very significant effect at 12 MAP. The highest average number of tillers at 12 MAP obtained at Bongan accessions (9.75 tillers), but not significantly different from Kota Bangun accessions (6.11 tillers) and Jempang (6.67 tillers), while the lowest average number of tillers was obtained at Anggana accessions (1.57 tillers) but not significantly different from Muara Wis accessions (3.33 tillers). In the second experiment, the results of the analysis showed that the treatment of accession had no significant effect on increasing the diameter of the stem, increasing the length of the leaf, and increasing the number of leaves, but significantly affected the increase in plant height at 2 MAP. In general, it can be seen that seedlings that are still young (0 - <3 months) when used as planting material have a better percentage of life and growth compared to older seeds (3 - <5 months) and (5 - <7 months).